2021
DOI: 10.1001/jamanetworkopen.2021.40352
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Cause of Death Among Youths Previously Incarcerated in the Juvenile Legal System

Abstract: Key Points Question Are youths with a history of incarceration at increased risk of early mortality compared with youths with no history of incarceration? Findings In this cohort study of 3645 previously incarcerated youths, the all-cause mortality rate was 5.9 times higher in previously incarcerated youths than the rate observed in general population, Medicaid-enrolled youths. Homicide was the leading cause of death among formerly incarcerated youths, acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…However, it is important to note that studies in the literature show connections between accelerated pace of biological aging, risk factors, and disease outcomes in African American research participants (e.g., [ 51 ]). Second, the rate of death among LCP offenders in our sample was relatively low, whereas American studies report elevated rates of early death for LCP offenders [ 48 , 63 ]. Thus, death rates may somewhat differ according to availability of free universal healthcare and degree of firearms control.…”
Section: Discussionmentioning
confidence: 76%
“…However, it is important to note that studies in the literature show connections between accelerated pace of biological aging, risk factors, and disease outcomes in African American research participants (e.g., [ 51 ]). Second, the rate of death among LCP offenders in our sample was relatively low, whereas American studies report elevated rates of early death for LCP offenders [ 48 , 63 ]. Thus, death rates may somewhat differ according to availability of free universal healthcare and degree of firearms control.…”
Section: Discussionmentioning
confidence: 76%
“…, 51]. Second, the rate of death among LCP offenders in our sample was relatively low, whereas American studies report elevated rates of early death for LCP offenders [48,63]. Thus, death rates may somewhat differ according to availability of free universal healthcare and degree of firearms control.…”
Section: Actionable Recommendations: What Can Be Done?mentioning
confidence: 81%
“…Two complementary studies published in JAMA Network Open shed light on the association between incarceration and mortality (Bovell-Ammon et al and Ruch et al). Bovell-Ammon et al explore the association between incarceration and mortality using cohort data from the National Longitudinal Survey of Youth (NLSY79) from 1979 to 2018.…”
mentioning
confidence: 99%
“…The research of Ruch et al followed up a cohort of incarcerated youth in Ohio from 2010 to 2017 to investigate how their mortality rates contrast with nonincarcerated peers who were enrolled in Medicaid. They found that the all-cause mortality rate for incarcerated youth was significantly higher than that for Medicaid-enrolled youth (adjusted incidence rate ratio, 5.91; 95% CI, 4.90-7.13), with Black youth more likely to die from homicide, while White youth were more likely to die at higher rates from suicide and drug overdose.…”
mentioning
confidence: 99%
See 1 more Smart Citation